2013
DOI: 10.22323/2.12030204
|View full text |Cite
|
Sign up to set email alerts
|

The object of art in science: science communication via art installation

Abstract: Science is part of our everyday live; so is art. Some art installations that link the two require the active presence of the spectator. Thereby they help to raise the awareness, promote understanding, and generate an emotional response from the public. This project rests on the public participation model that seeks to explore the connection between art installations and science communication through experiential learning. In order to test the effectiveness of an art installation communicating science two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…The evidence from literature that I have exposed in this paper, together with empirical work that I published in previous work (Negrete, 2009;Negrete and Lartigue, 2010;Rios and Negrete 2013;Negrete, 2014;Lartigue and Negrete 2016) suggest that narratives represent an interesting tool for science communication to convey science not only in an attractive and reliable format, but also in a memorable way.…”
Section: Final Notementioning
confidence: 52%
See 1 more Smart Citation
“…The evidence from literature that I have exposed in this paper, together with empirical work that I published in previous work (Negrete, 2009;Negrete and Lartigue, 2010;Rios and Negrete 2013;Negrete, 2014;Lartigue and Negrete 2016) suggest that narratives represent an interesting tool for science communication to convey science not only in an attractive and reliable format, but also in a memorable way.…”
Section: Final Notementioning
confidence: 52%
“…In previous work (Negrete, 2009;Negrete and Lartigue, 2010;Rios and Negrete 2013;Negrete, 2014;Lartigue and Negrete 2016) I provided empirical evidence suggesting that narratives represent a memorable text format. In this opportunity my intention is to examine what has been reported in literature regarding features of the memory process that contributes to make narratives a memorable device.…”
Section: Objective and Methodologymentioning
confidence: 93%
“…In previous work (Negrete, 2009(Negrete, , 2013(Negrete, , 2014Negrete and Lartigue, 2010;Rios and Negrete 2013;Lartigue and Negrete 2016), we provided empirical evidence suggesting that science can be communicated and learnt through narratives, and that this represents a more enjoyable way of learning compared to traditional texts. In particular, we found that narrative information is retained for lengthier periods than factual information in long-term memory.…”
Section: Objective and Methodologymentioning
confidence: 61%
“…[Lanza y Negrete, 2007;Rios y Negrete, 2013;Lartigue y col., 2016]. Según Gardner [2001], en su teoría sobre las inteligencias múltiples, la narrativa es una de las maneras en que la complejidad puede ser presentada y comunicada.…”
Section: Introductionunclassified